Cardiotoxic and Cardioprotective Effects of Methylene Blue in the Animal Model of Cardiac Ischemia and Reperfusion - Hezio Jadir Fernandes Junior; Erisvaldo Amarante de Araújo; José Antônio Machado Junior; Fabio Marinho Lutz Motta; Gabriela Ferrazzano Guarize; Lucas Chen Cheng; Junaid Tantray; Jand Venes Rolim Medeiros; Lucas Antonio Duarte Nicolau; Adriano Henrique Pereira Barbosa; Adriano Caixeta; Isadora S. Rocco; et al. (Biomedicines, 2024)
Background/Objectives: Treatment of patients with myocardial ischemic diseases crucially involves cardiac reperfusion (CR). However, oxidative stress and tissue lesions caused by CR may also lead to lethal complications, such as arrythmias and vasoplegic syndrome (VS). Although methylene blue (MB) has long been used to treat VS due to cardiac ischemia and reperfusion (CIR) and/or surgery because of its vascular effects, MB’s effects on the heart are unclear. Therefore, we investigated the potential cardioprotective or arrhythmogenic effects of MB in an animal model of CIR. To this end, 12–16-week-old male Wistar rats were divided into four experimental groups: (a) rats subjected to SHAM surgery with no ischemia; (b) rats subjected to CIR and treated with a vehicle (SS + CIR); and (c) rats subjected to CIR and treated with 2 mg/kg i.v. MB before ischemia (MB + ISQ) or (d) after ischemia but before reperfusion (ISQ + MB). An ECG analysis was used to evaluate the incidence of ventricular arrhythmias (VAs), atrioventricular blocks (AVBs), and lethality (LET) resulting from CIR. After CIR, rat hearts were removed for histopathological analysis and lipid hydroperoxide (LH) measurements. Results: The incidence of VA, AVB, and LET was significantly increased in the MB + ISQ group (VA = 100%; AVB = 100%; LET = 100%) but significantly reduced in the ISQ + MB group (VA = 42.8%; AVB = 28.5%; LET = 21.4%) compared with the SS + CIR group (VA = 85.7%; AVB = 71.4%; LET = 64.2%). LH concentration was significantly reduced in both MB-treated groups, but myocardial injuries were increased only in the MB + ISQ group when compared with the SS + CIR group. Conclusions: These results indicate that MB produces a biphasic effect on CIR, with cardiotoxic effects when administered before cardiac ischemia and cardioprotective effects when administered after ischemia but before cardiac reperfusion.